Analysis of Tear Function Outcomes following Collagen Cross-Linking Treatment in Ectatic Corneas. (14th March 2022) - Wang, Xiu; Bai, Xue; Jin, Chengcheng; Zhao, Liqiong; Wei, Ruihua
Abstract : Purpose . To analyze tear function outcomes following collagen cross-linking (CXL) treatment in ectatic corneas. Methods . Fifty-seven eyes of 34 patients were included, and patients with keratoconus who underwent epithelium-on (epi-on) or epithelium-off (epi-off) CXL were evaluated. The following tests were performed preoperatively and at 1, 3, 6, and 12 months postoperatively: best-corrected visual acuity (BCVA), maximum keratometry value (Kmax), ocular surface disease index (OSDI) questionnaire, slit-lamp examination, tear meniscus height, first noninvasive Keratograph breakup time (1st NIKBUT), average NIKBUT, and bulbar redness. Results . BCVA improved in both epi-on and epi-off groups at most follow-up points, but was not significantly different between groups. At 12-month follow-up, Kmax in the epi-on and epi-off groups improved after CXL, but there was no significant difference between the groups. The OSDI in both groups decreased after operation compared with before surgery, and there was no significant difference between the two groups. Comparing the two groups, only the change in the tear meniscus height at 6 months postoperatively was statistically significant, and the pre- and postoperative values of the two groups were within the normal range (>0.20 mm). The change was small and had no clinical significance. There was no change in the 1st NIKBUT and average NIKBUT between the epi-on and epi-off groups. A change in bulbar redness was significantly better in the epi-off group than in the epi-on group at 3 months postoperatively. Comparing the effects at 1 year postoperatively, both groups had positive results in OSDI, NIKBUT, tear meniscus height, and bulbar redness. Conclusion . Both epi-on and epi-off CXL can control the progression of keratoconus, although epi-off CXL is more effective. Both methods have a positive effect on dry eye, which can improve the condition of the tear film and reduce dry eye symptoms in patients with keratoconus.